Developing an instrument for Iranian EFL learners' listening comprehension problems and listening strategies - Noroozi, Sara; Tam, Shu Sim; Nimehchisalem, Vahid; Zareian, Gholamreza (Australian International Academic Centre, 2014)
In the body of literature on listening strategies to EFL learners, what seems to be lacking is that the focus is on teaching listening strategies to learners with little attention to their listening comprehension problems. No local research has been conducted on the nature of the Iranian tertiary level students' EFL listening comprehension problems or strategies. Therefore, no instrument is available to investigate these constructs. This paper reports the findings of a study that made an attempt to develop and test an instrument that will aid researchers identify students’ specific listening problems and listening strategy repertoire. The instrument was developed by integrating and validating the available instruments in the related literature. The two developed questionnaires were: the Listening Comprehension Problems Questionnaire (LCPQ) and the Listening Strategy Use Questionnaire (LSUQ). Problems related to designing and testing this instrument is shared and the modifications made to it are presented. The instrument is expected to be useful for researchers interested to study the area of EFL listening in a similar setting.